Characterization of the energy‐dependent response of riometer absorption. Issue 1 (8th January 2015) - Kellerman, A. C.; Shprits, Y. Y.; Makarevich, R. A.; Spanswick, E.; Donovan, E.; Reeves, G.
Abstract Ground‐based riometers provide an inexpensive means to continuously remote sense the precipitation of electrons in the dynamic auroral region of Earth's ionosphere. The energy‐dependent relationship between riometer absorption and precipitating electrons is thus of great importance for understanding the loss of electrons from the Earth's magnetosphere. In this study, statistical and event‐based analyses are applied to determine the energy of electrons to which riometers chiefly respond. Time‐lagged correlation analysis of trapped to precipitating fluxes shows that daily averaged absorption best correlates with ∼60 keV trapped electron flux at zero‐time lag, although large variability is observed across different phases of the solar cycle. High‐time resolution statistical cross‐correlation analysis between signatures observed by riometer stations, and assuming electron motion due to gradient and curvature drift, results in inferred energies of 10–100 keV, with a clear maximum in occurrence for 40–60 keV electrons. One event is considered in detail utilizing riometer absorption signatures obtained from several stations. The mean inferred energies for the initial rise time and peak of the absorption after correction for electric field effects were ∼70 keV and ∼60 keV, respectively. The analyses presented provide a means to characterize the energy of electrons to which riometers are responding in both a statistical sense and during the evolution of individual events.